Opportunities and challenges for sustainable production and marketing of gums and resins in Ethiopia - Lemenih, Mulugeta; Kassa, H. (Center for International Forestry Research, 2011)
This publication is intended to serve researchers and teachers as well as development practitioners. It was prepared based on requests from CIFOR’s national partners in Ethiopia and the region to compile existing information and help address the lack of documents available for teaching graduate and undergraduate students about the management of forests in dryland areas in general, and the production and marketing of gums and resins in particular. By describing the current status of the dry forest resource base and the production and marketing of gums and resins, this publication contributes toward filling the existing knowledge gap. Chapter 1 presents an overview of challenges and forest-based opportunities in the drylands of Ethiopia. Chapter 2 describes in detail the resource base of gums and resins as well as the challenges to their productivity. Chapter 3 discusses production, handling and quality control, while Chapter 4 addresses value-added processing and the marketing of gums and resins. Finally, Chapter 5 summarises challenges and opportunities as well as actions for sustainable gum and resin production